Studi Pengaruh Radius Kelengkungan terhadap Efektifitas Kekangan pada Kolom Persegi dengan Perkuatan FRP - Anang Kristianto; Yosafat Aji Pranata; Noek Sulandari (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Revised code of earthquake-resistant building design from SNI 1726:2012 to SNI 1726:2019 as a result of changes in the earthquake magnitude that occurred in recent years and developments in earthquake engineering research resulted in many building structural elements should be strengthened, especially on column elements. One of the most adopted strengthening techniques for enhancing the performance of existing RC columns consists of wrapping a member with CFRP (Carbon Fiber Reinforcement Polymer) sheets, inducing a passive confinement action capable of increasing the columns axial strength and displacement capacity. The use of CRFP as strengthening on square columns in existing buildings should consider various factors, including the column corner radius and the width of the strip of FRP required if not using full wrapping. This paper presents the confinement stresses analysis at the different radius of curvature of the square column corner and analyzes the correlation of stress-strain in the cross-section using data from various existing studies. An experimental study will also be done by axial loading test FRP column (100mm x 100mm x 200mm) with several different curvature radii. The results of the axial compression test to the specimens found that the effect of curvature is quite significant for confinement effectiveness at r/b < 0.15. Based on this experiment,  a slight increase of the axial capacity on the column specimens with radius curvature r=0mm and r=10mm ( below r=13mm, the smallest radius allowed by the code). Rectangular concrete columns strengthened by FRP with r/b < 0.15 could not be effective to the confined concrete core due to stress concentration at the corner.